White Collar Jobs Move Overseas: Implications for States. - Hira, Ron (Spectrum: Journal of State Government)
High technology white collar jobs are moving overseas at an accelerating pace. States with high concentrations of information technology workers have experienced the most negative effects. States that want to create and attract high technology industries and jobs should consider risks from offshore outsourcing. Reprinted by permission of the publisher.